2012
DOI: 10.1073/pnas.1207889109
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell model recapitulates pathologic hallmarks of Gaucher disease

Abstract: Gaucher disease (GD) is an autosomal recessive disorder caused by mutations in the acid β-glucocerebrosidase gene. To model GD, we generated human induced pluripotent stem cells (hiPSC), by reprogramming skin fibroblasts from patients with type 1 (N370S/N370S), type 2 (L444P/RecNciI), and type 3 (L444P/L444P) GD. Pluripotency was demonstrated by the ability of GD hiPSC to differentiate to all three germ layers and to form teratomas in vivo. GD hiPSC differentiated efficiently to the cell types most affected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 35 publications
5
108
0
2
Order By: Relevance
“…We generated and studied primary macrophages (hMacs) that were differentiated from monocytes taken from patients with Gaucher disease. However, the amount of blood needed, especially from infants with Gaucher disease type 2, and the limited yield of macrophages prompted us to create induced pluripotent stem cells (iPSCs) from dermal fibroblasts taken from patients to generate and evaluate a clonal supply of macrophages (iMacs) (13). Here, we use hMacs and iMacs to evaluate the ability of the noninhibitory chaperone molecule NCGC00188758 to reverse the disease phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…We generated and studied primary macrophages (hMacs) that were differentiated from monocytes taken from patients with Gaucher disease. However, the amount of blood needed, especially from infants with Gaucher disease type 2, and the limited yield of macrophages prompted us to create induced pluripotent stem cells (iPSCs) from dermal fibroblasts taken from patients to generate and evaluate a clonal supply of macrophages (iMacs) (13). Here, we use hMacs and iMacs to evaluate the ability of the noninhibitory chaperone molecule NCGC00188758 to reverse the disease phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Neural crest progenitors were also derived from iPSCs and compared with those from hESCs, followed by differentiation to functional Schwann cells [104]. More than the therapeutic use of neural progenitors derived from hiPSCs, this in vitro cell-based technology is in the spotlight to reproduce cellular models of poorly understood diseases -such as Down syndrome, Friedreich's ataxia, Gaucher disease [105][106][107], amyotrophic lateral sclerosis [108], spinal muscular atrophy [109], Parkinson's disease [110,111], schizophrenia [112], Huntington's disease [110], and Alzheimer's disease [113]. Furthermore, correction of genetic mutations in disease-specific iPS cells can rescue phenotypes in cultured cells [111,114] or in mouse models of human diseases, such as sickle cell anemia [115].…”
Section: Differentiation Of Human-induced Pluripotent Stem Cells (Ipsmentioning
confidence: 99%
“…They also demonstrated defective phagocytosis in these iPSC-derived GMs [11] , and more recently showed that these cells exhibit greatly increased secretion of the pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 in response to lipopolysaccharide (LPS) treatment [12] . These results reflect the increased expression of these cytokines observed in some patients with type 1 GD [2,4] .…”
Section: Research Highlightmentioning
confidence: 99%
“…Panicker et al derived iPSC lines from patients with all three forms of GD [11,12] . They also demonstrated defective phagocytosis in these iPSC-derived GMs [11] , and more recently showed that these cells exhibit greatly increased secretion of the pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 in response to lipopolysaccharide (LPS) treatment [12] .…”
Section: Research Highlightmentioning
confidence: 99%